Between Assistance and Dependence: Adolescent EFL Learners’ AI Use in Informal Islamic Education - Syahrussalamah, Anis Khoirunnisa; Sulaeman, Dedi; Imani, Anugrah (UICELE, 2026)
This study examines how adolescent EFL learners in a low-exposure informal Islamic education context perceive and use AI tools for English language learning. Using a survey-based descriptive design, data were collected from 41 learners aged 11-17 at a Taman Pendidikan Qur’an (TPQ) in semi-urban West Java, Indonesia, via a bilingual questionnaire administered in April-May 2026. Findings show that Google Translate dominates AI tool use (90%), with ChatGPT adopted by 54% of respondents. Three recurring attitudinal tensions emerged: assistance versus dependence, curiosity versus caution, and informal use versus limited AI literacy. A supplementary comparison of ChatGPT users (n = 22) and non-users (n = 19) indicates that ChatGPT users report lower writing confidence (9% vs. 32%) yet higher cognitive off-loading awareness (59% vs. 47%). A near-unanimous demand for guided AI instruction (71%; zero disagreement) points to an unmet institutional need. These findings suggest that digital access to AI tools does not automatically produce critical AI literacy and that structured instructional scaffolding is needed in low-exposure EFL contexts.